2017
DOI: 10.1002/2017gl074646
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of minimal carbon sequestration in the productive Amundsen Sea polynya

Abstract: The Amundsen Sea polynya (ASP) is reportedly the most productive among the coastal polynyas around Antarctica. However, observational constraints limit our understanding of the biological pump and carbon cycle in the ASP. We measured various carbon‐related parameters such as primary production, bacterial production, sinking flux of particulate organic carbon (POC), and accumulation of organic carbon in the sediment as well as hydrographic parameters during field observations and by instrument moorings. Over 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…In this way, the magnitude of deep-DOC consumption in the water column can be calculated. We estimated the fractions of fresh-DOC and deep-DOC as follows: where Δ 14 C deep = −492 ± 20‰ (mean value of CDW previously reported at 54°S, 176°W and 55.6°S, 84.7°E 25,26 ) and Δ 14 C fresh = −149 ± 10‰ from surface water DIC values 24 . Taking the surface sample at ASP-2014 with a Δ 14 C value of −285‰ as an example, we calculated that it contained 39% deep-DOC (25 ± 4 μM) and 61% fresh-DOC (39 ± 5 μM).…”
Section: Doc Cycling In the Amundsen Sea Previous Studies Have Repormentioning
confidence: 99%
“…In this way, the magnitude of deep-DOC consumption in the water column can be calculated. We estimated the fractions of fresh-DOC and deep-DOC as follows: where Δ 14 C deep = −492 ± 20‰ (mean value of CDW previously reported at 54°S, 176°W and 55.6°S, 84.7°E 25,26 ) and Δ 14 C fresh = −149 ± 10‰ from surface water DIC values 24 . Taking the surface sample at ASP-2014 with a Δ 14 C value of −285‰ as an example, we calculated that it contained 39% deep-DOC (25 ± 4 μM) and 61% fresh-DOC (39 ± 5 μM).…”
Section: Doc Cycling In the Amundsen Sea Previous Studies Have Repormentioning
confidence: 99%
“…The export flux of C org formed by a Phaeocystis bloom is twofold slower than that formed by a diatom bloom (DeJong et al, 2017), and thus the contribution of P. antarctica cells to total export flux below the photic zone declines dramatically (Reigstad and Wassmann, 2007). Indeed, in the ASP, most photosyntheticallyproduced particulate organic carbon (POC) (>95%) exported from the surface layer is converted to suspended POC and/or dissolved carbon within the top 400 m of the water column (Ducklow et al, 2015;Lee et al, 2017). In addition, direct rate measurement conducted in this study also demonstrated that, despite high primary production (110 mmol C m −2 d −1 ) in the Phaeocystis-dominated water column of the ASP, benthic C org mineralization (average, 2.1 mmol C m −2 d −1 ) accounted for only 1.9% of primary production, which was strikingly lower than that measured in other less productive polar regions (Kim et al, 2016).…”
Section: Organic Substrates Control Spatial Distribution Of Planctomymentioning
confidence: 99%
“…Due to the inflow of warm circumpolar deep water (CDW), glaciers near the Amundsen Sea (AS) are undergoing the highest rates of melting and thinning on the Antarctic continent (Rignot, 2008;Jenkins et al, 2010;Jacobs et al, 2011). Consequently, as global warming continues, the heat flux intensity of the CDW may stimulate ice melting, which results in changes in phytoplankton productivity and community composition (Deppeler and Davidson, 2017), thereby regulating the function of the ASP in carbon sequestration (Thoma et al, 2008;Lee et al, 2017). The composition and metabolic activities of benthic microbial communities are ultimately determined by the quality and quantity of the organic matter supplied from the overlying water column (Franco et al, 2007;Bienhold et al, 2012;Ruff et al, 2014;Hoffmann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fixed by phytoplankton in the water column is transferred to higher trophic levels, and finally, is exported from the system to the deep ocean [7]. However, intriguingly, in the Amundsen Sea dominated by P. antarctica , most of the organic carbon from primary production does not reach the sediment; instead, it is actively recycled and mineralized in the water column via microbial loop [811]. Indeed, higher heterotrophic bacterial production, accounting for ca.…”
Section: Introductionmentioning
confidence: 99%